ANALISIS PENGARUH PRODUK, HARGA, TEMPAT, DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PADA PERUSAHAAN PT POS INDONESIA CABANG KANTOR POS PLEMBURAN SLEMAN - Supriyadi, Nurdin (JURNAL EKOBIS DEWANTARA, 2024)
This study aims to determine the influence of Product, Price, Place, and Promotion on Customer Loyalty at PT Pos Indonesia, Plemburan Branch, Yogyakarta. The research employed a quantitative approach using a survey method through questionnaire distribution. The sampling technique used was accidental sampling, with a total of 80 respondents. The research instrument was developed using a Likert scale from 1 to 5, and the data were analyzed using multiple linear regression with the aid of SPSS software. The results showed that both partially and simultaneously, the variables of Product, Price, Place, and Promotion had a positive and significant influence on Customer Loyalty. Among the variables, Place had the most dominant influence. The Adjusted R Square value of 0.345 indicates that the four variables explain 34.5% of the variation in customer loyalty, while the remaining 65.5% is influenced by other variables not examined in this study. These findings provide important implications for company management in enhancing customer loyalty through more effective marketing mix strategies.